Peningkatan Akhlak Anak Usia Dini Berbasis Pendidikan Karakter Melalui Program Cinta Rasul Pada Siswa Taman Kanak-Kanak - Adam Jakinur; Muhammad Ari Khairan; Rafki Parifia; Yogi Permana; Wismanto (IHSANIKA : Jurnal Pendidikan Agama Islam, 2024)
ABSTRACT Education through official educational institutions that first forges our children's morals is Kindergarten. It is this institution that will first shape the character of our children after they receive basic education in their own homes with their own father and mother teachers. So every parent should know how to choose an educational institution that is in line with the education provided to their children while at home. Several kindergartens run Islamic-based character education called the Rosul Love Program. The teacher's role as a guide is to guide children in ablution, as an example of how to say good greetings, as a source of knowledge about God's creation, and as a teacher learner observing children's attitudes and behavior. Children keep the school environment clean by throwing rubbish in the right place. Teachers and children together build an Islamic social environment and respect each other. The aim of the research is to describe the picture of Islamic-based character education, the role of teachers, the environment, and obstacles to implementing character education activities in kindergarten. This research method is a descriptive qualitative method with a Library Research approach. The main data sources come from books, magazines and the latest journal articles related to this research theme. The results of this research are that most kindergartens view character education as Islamic-based character education, namely character education that is based on the moral foundations of the Islamic religion which includes aspects of aqidah, worship, society, morals, personality, intellectuality and physicality. As an embodiment of character education, some kindergartens run a learning program called the Rosul Love Program, which is a learning program that seeks to instill Rosulullah's example in the children in the kindergarten. These examples include leadership, honesty, speaking softly, respecting parents, respecting teachers, being responsible and independent.